Modern Approaches in Immunoprophylaxis of Infectious Diseases During Pregnancy - Leyla S. Namazova-Baranova; Marina V. Fedoseenko; Liliya R. Selimzyanova; Tatiana A. Kaliuzhnaia; Firuza Ch. Shakhtakhtinskaya; Svetlana V. Tolstova; Arevaluis M. Selvyan (Union of pediatricians of Russia, 2023)
Every year more countries recommend vaccination for pregnant women. Nowadays, the spectrum of vaccines that can be used during pregnancy is expanding. Experts of the Union of Pediatricians of Russia have completely updated the section about the pregnant women immunoprophylaxis within updating clinical guidelines on normal pregnancy management. This section is presented in the following article.